Data Governance and Privacy Challenges in Digital Public Services: Evidence from Eastern Samar, Philippines - Septian Bayu Kristanto; Rodven Cases; Hyacinth Taon; Diane Elizabeth Mabansag; Norlyn Joy Fidelino (Jurnal Inspektorat, 2026)
This study examines the challenges of data governance and privacy in digital public service delivery in Eastern Samar, Philippines, a region characterized by geographic isolation, economic vulnerability, and limited digital infrastructure. Using a mixed-methods approach, the research combines a survey of 300 residents with in-depth interviews involving 20 key stakeholders, including government officials, civil society representatives, and ICT practitioners. The findings reveal a significant gap between national data governance frameworks and their implementation at the local level. While policies such as the Data Privacy Act provide a formal foundation, their practical application remains constrained by low digital literacy, weak institutional capacity, and inadequate infrastructure. The study also identifies a pervasive trust deficit, as many citizens express concerns regarding data misuse and lack confidence in government data management practices. Despite these challenges, there is strong public interest in engaging with digital public services, particularly among younger populations, indicating potential for more inclusive digital transformation. Practically, the study suggests that local governments should prioritize targeted digital literacy programs, strengthen institutional capacity through training and resource allocation, and enhance transparency mechanisms to build public trust. Furthermore, the integration of accountability frameworks, such as clear data governance procedures and oversight systems, is essential to ensure ethical data management and sustainable digital governance. These findings contribute to the broader discourse on governance and accountability in digital public service delivery, particularly in underdeveloped and disaster-prone regions.